1987
DOI: 10.1042/bj2470789
|View full text |Cite
|
Sign up to set email alerts
|

The effects of recombinant tumour necrosis factor (cachectin) on metabolism in isolated rat adipocyte, hepatocyte and muscle preparations

Abstract: Tumour necrosis factor (TNF) did not stimulate lipolysis in isolated rat adipocytes, though preincubation with TNF increased adrenaline-stimulated fatty acid release. Glycogenolysis, gluconeogenesis and ketogenesis in isolated rat hepatocytes were not influenced by TNF in short-term (30-60 min) incubations. TNF stimulated 14CO2 production from [U-14C]glucose in rat hemidiaphragm preparations, but lactate production and alanine release were not significantly altered. It is concluded that TNF does not regulate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 21 publications
4
22
0
Order By: Relevance
“…The present study showed that TNF-␣ did not alter gluconeogenesis in hepatocytes isolated from adult rats, confirming the findings of other investigators (17). Hill and McCallum (6) concluded from their in vivo studies that TNF-␣ was a transcriptional regulator of PEPCK and suppressed PEPCK function.…”
Section: Tnf␣ Effects On Hepatocyte Gluconeogenesissupporting
confidence: 92%
See 1 more Smart Citation
“…The present study showed that TNF-␣ did not alter gluconeogenesis in hepatocytes isolated from adult rats, confirming the findings of other investigators (17). Hill and McCallum (6) concluded from their in vivo studies that TNF-␣ was a transcriptional regulator of PEPCK and suppressed PEPCK function.…”
Section: Tnf␣ Effects On Hepatocyte Gluconeogenesissupporting
confidence: 92%
“…These results suggest that TNF-␣ decreases gluconeogenesis in both newborn and adult animals. In hepatocytes isolated from adult rats, however, gluconeogenesis is not altered after a short incubation with TNF-␣ (17). TNF-␣ effects on glucose metabolism in hepatocytes isolated from newborns are not well known.…”
mentioning
confidence: 96%
“…It has also been shown that prostaglandin E2 production was increased by these macrophage secretory products and an inhibitor of the cycloocygenase pathway, indomethacin, partially attenuated the stimulation in skeletal muscle protein degradation (Baracos et al, 1983 (Moldawer et al, 1987;Goldberg et al, 1988). Likewise, the involvement of TNF-a on catabolism of proteins has been demonstrated by some studies in vivo (Warren et al, 1987;Flores et al, 1989;Fong et al, 1989) and in vitro Charters & Grimble, 1989) and refuted in others (Kettelhutt & Goldberg, 1988;Moldawer et al, 1987;Rofe et al, 1987;Michie et al, 1988). Nevertheless, the capacity of IL-1 and TNF to cause either weight loss or anorexia in animals has often been noted (Stovroff et al, 1988;Hellestein et al, 1989;Fong et al, 1989;Michie et al, 1988; (Dinarello et al, 1986a), and polyclonal rabbit anti-sera to rhIL-1-a and rhIL-1-P (Dinarello et al, 1986b) were generously provided by Dr Charles A. Dinarello, Tufts University/New England Medical Center (Boston, MA).…”
Section: Discussionmentioning
confidence: 92%
“…The observed differences may reflect the release of other unidentified cytokines in response to endotoxin which promote net protein catabolism (33,34) and/or differences in the mode of administration (i.e., single bolus 10-9 M (48). In vitro, TNF or IL-I did not affect lactate or alanine release, by rat diaphragms within 2 h, although glucose oxidation was mildly stimulated (49). Marked acceleration of glucose transport, glucose transporter synthesis, lactate production and glycogenolysis was observed in a muscle derived cell line (L-6 myotubes) upon exposure to TNF, but not IL-1 (50).…”
Section: Resultsmentioning
confidence: 99%